2013
DOI: 10.1371/journal.ppat.1003180
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Activation of Akt Elicits Mitochondrial Dysfunction to Block Plasmodium falciparum Infection in the Mosquito Host

Abstract: The overexpression of activated, myristoylated Akt in the midgut of female transgenic Anopheles stephensi results in resistance to infection with the human malaria parasite Plasmodium falciparum but also decreased lifespan. In the present study, the understanding of mitochondria-dependent midgut homeostasis has been expanded to explain this apparent paradox in an insect of major medical importance. Given that Akt signaling is essential for cell growth and survival, we hypothesized that sustained Akt activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(82 citation statements)
references
References 106 publications
2
79
0
Order By: Relevance
“…S2). PGC-1α promotes mitochondrial biogenesis through expression of mitochondrial proteins and activation of p38/MAPK pathway (Acín-Pérez et al, 2008;Luckhart et al, 2013). These results confirmed that PGC-1α has an important role in prompting ATP production and clearing excessive ROS, and mitochondrial respiratory supercomplexes also enhance ATP and decrease ROS through structure variant, so we suggested that PGC-1α may be a positive regulator of mitochondrial respiratory supercomplex formation, but the mechanism remains unclear.…”
Section: Discussionsupporting
confidence: 63%
“…S2). PGC-1α promotes mitochondrial biogenesis through expression of mitochondrial proteins and activation of p38/MAPK pathway (Acín-Pérez et al, 2008;Luckhart et al, 2013). These results confirmed that PGC-1α has an important role in prompting ATP production and clearing excessive ROS, and mitochondrial respiratory supercomplexes also enhance ATP and decrease ROS through structure variant, so we suggested that PGC-1α may be a positive regulator of mitochondrial respiratory supercomplex formation, but the mechanism remains unclear.…”
Section: Discussionsupporting
confidence: 63%
“…number of studies have demonstrated the importance of these genes or pathways in mosquito defense against parasites or viruses [16][17][18][19][20][29][30][31]. Manual analysis showed overall agreement with the automated annotation and improved the gene models in some cases (Additional file 2).…”
Section: Immunity Genesmentioning
confidence: 78%
“…Our understanding of the interactions between An. stephensi and the malaria parasites is rapidly improving [15][16][17][18][19][20]. Thus An.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of FOXO has also been shown to decrease mitochondrial and cytoplasmic antioxidants (43), so it is possible that silencing FOXO may reduce midgut oxidative stress by increasing the level of antioxidants, and this would be beneficial to the parasite. Interestingly, activation of the same pathway in the absence of Pfs47, when JNK signaling is active, triggers a strong apoptotic response that greatly limits infection.…”
Section: Discussionmentioning
confidence: 99%